THE BENEFITS AND IMPORTANCE OF PHYSICAL ACTIVITY IN COMBATING OBESITY AMONG CHILDREN-A LITERATURE REVIEW - Dan-Alexandru SZABO; Andreea ILIEȘ; Andreea Bianca STOICA (Editura Universităţii din Oradea, 2021)
The development of boyhood overweight is usually related to maintaining the pathophysiological state in adulthood. Childhood overweight is characterized as the abnormal buildup of body weight in adipose tissue during childhood, which harms health. Increased physical behavior appeared linked to various health benefits, ranging from improved lipid and glucose homeostasis to endothelial function. Such health outcomes are usually independent of BMI changes. The prevention of boyhood adiposity is a global health priority. Because obesity is a complex condition, effective obesity prevention strategies must consider various factors (personal, environmental, and socio-economic). This article aims to review the benefits, importance, and advertising of physical behavior to children and emphasize the prevention and treatment of childhood obesity.